THE RECONSTRUCTION OF THE CRIMINAL JUSTICE SYSTEM FOR ADDRESSING CORRUPTION CRIME IN THE FRAMEWORK OF SUPPORTING NATIONAL DEVELOPMENT - Maroni Maroni; Nenny Dwi Ariani; Dheka Ermelia Putri (Cepalo, 2021)
The urgency for criminal justice system reconstruction of the corruption is given the legal gap in eradicating corruption law if it is only carried out by the Regional Corruption Court, which is domiciled in the Capital Province. Because the Corruption Court’s working area is so broad, it is because many corruption cases to be tried, it will also require large fees and a large number of judges, and ideally, it will take a long time in the process of examining. Meanwhile, on the other hand, there is an obligation for the corruption case settlement by the Corruption Court to be carried out quickly, simply and at low cost. This paper’s problems are: (a) Why is it important to reconstruct the Corruption Criminal Justice System? (b) What is the ideal construction of the Corruption Criminal Justice System to support national development in Indonesia? The research method is qualitative with juridical normative and sociological approaches, especially in collecting primary data to reconstruct the corruption criminal justice system. This research shows that the ideal construction of the corruption court system is to support National Development, namely the relative competence of the Regional Corruption Court, which is not limited by the administrative area of a province. The Republic of Indonesia’s administrative area consists of various Provinces and Regencies/Cities. In these conditions, ideally, the relative competence of a Corruption Court can also examine corruption cases in districts/cities close to the Corruption Court, even though they are located in a different province from the domicile of a Corruption Court.